Cerebral blood flow alterations in the precuneus of Alzheimer's disease using arterial spin labeling: A systematic review and meta-analysis - Sadegh Ghaderi; Sana Mohammadi; Farzad Fatehi (Brain Research Bulletin)
Background: Alzheimer's disease (AD) is a neurodegenerative disease characterized by decline in brain hypoperfusion, particularly in the precuneus, which is critical for higher cognitive function. Arterial spin labeling (ASL) studies have demonstrated hypoperfusion patterns; however, these findings have not been systematically analyzed. Therefore, there is a need to synthesize evidence to validate the diagnostic utility of ASL. Methods: This review was conducted in accordance with the PRISMA guidelines. Databases including PubMed, Scopus, Web of Science, and Embase were searched from 2000 to December 2023. A random-effects model was used to perform statistical analysis by calculating the standardized mean difference (SMD) (Cohen's d). Subgroup and sensitivity analyses were conducted. Results: Thirteen studies including 324 patients with AD and 317 controls were included. Significant hypoperfusion was found in the precuneus of patients with AD compared with controls (SMD: −1.12; 95 % CI, −1.52 to −0.72). Subgroup analysis revealed variations based on several factors, such as age, gender (sex), geography, technique, risk of bias, and imaging parameters. The study found greater effects in the group of 70–75 year-olds, studies with a higher proportion of males, Asian populations, the 3D pCASL method, 8-channel coils, and lower field strengths. Studies with lower risk of bias showed smaller effects. These differences highlight the importance of considering influential factors in the design and interpretation, while validating generally consistent hypoperfusion in patients with AD. Conclusions: The meta-analysis confirmed significant hypoperfusion in the precuneus of patients with AD, consistent with hypometabolic patterns.